1995
DOI: 10.1111/j.1365-2249.1995.tb03845.x
|View full text |Cite
|
Sign up to set email alerts
|

T cell activation by Theileria annulata-infected macrophages correlates with cytokine production

Abstract: SUMMARYA major feature of the pathology induced by Theileria annulata is acute lymphocytic proliferation, and this study investigates the mechanisms underlying the intrinsic ability of T. anniilata-infecXed monocyles to induce naive autoiogous T cells to proliferate. Different 7". aiinulata-'mkcted clones expressed different but constant levels of MHC class II, varying from < 10 x 10' to 1-5 x 10niolecules/celK as measured by saturation binding. However, no correlation was found between the level of MHC class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 22 publications
5
46
6
Order By: Relevance
“…In contrary with our results Brown et al (1995) showed that cells infected with T. annulata produce high levels of inflammatory cytokines especially TNF-a, which is a potent inducer of fever and also leads to anemia, muscle wasting and necrosis. T. annulata leads to production of various T cell-stimulatory and inflammatory cytokines which are responsible for immunopathological lesions observed during infection.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrary with our results Brown et al (1995) showed that cells infected with T. annulata produce high levels of inflammatory cytokines especially TNF-a, which is a potent inducer of fever and also leads to anemia, muscle wasting and necrosis. T. annulata leads to production of various T cell-stimulatory and inflammatory cytokines which are responsible for immunopathological lesions observed during infection.…”
Section: Discussioncontrasting
confidence: 99%
“…T. annulata leads to production of various T cell-stimulatory and inflammatory cytokines which are responsible for immunopathological lesions observed during infection. Increased production of IL-10 which showed similar findings with our results leads to reduced efficiency of immune response against infected cells (Brown et al 1995).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…BTT accounts for high mortality rates in dairy cattle with over 200 million animals exposed to risk (Radostits et al 1994;Sudan et al 2014). The global annual losses due to BTT are estimated to be of US$800 million (Brown et al 1995) while in India alone, the disease accounts for an approximate annual loss of US$384.3 million (Minjauw and McLeod 2003). To add up to the agony, animals with chronic cases of BTT show almost similar types of signs and symptoms with that of other arthropod vector borne diseases like trypanosomiosis, anaplasmosis and babesiosis.…”
Section: Introductionmentioning
confidence: 99%